Survei Tingkat Pemahaman Mahasiswa Prodi Pendidikan Bahasa dan Sastra Indonesia STKIP Paris Barantai terhadap Kurikulum Merdeka - Johar Amir; Sri Juniati (Journal on Education, 2024)
The purpose of this research is to determine the level of students' understanding of the independent curriculum. This research is quantitative descriptive research using survey methods. The research instrument is a questionnaire with questions given to students to determine their understanding of the independent curriculum. The sample for this research was all students from the 2021 Indonesian Language and Literature Education study program, totaling 68 students. The data analysis technique uses quantitative descriptive analysis. The results of the research show that the 2021 Indonesian Language and Literature Education Study Program students' understanding of the independent curriculum is mostly in the strongly agree or agree category. In detail, the percentage of research results based on data obtained in the strongly agree category was 5 students or (7%), the agree category was 59 students or (87%), the disagree category was 3 students or (4%), and the strongly disagree category as many as 1 student or (2%). Based on this, the researcher concluded that based on the results of a survey of students' understanding of the Indonesian language and literature education study program, STKIP Paris Barantai, they already understood the synchronization of independence. This is based on the answers chosen by respondents who chose the most Agree answer items